2015
DOI: 10.3892/or.2015.4234
|View full text |Cite
|
Sign up to set email alerts
|

Expression of RAP1B is associated with poor prognosis and promotes an aggressive phenotype in gastric cancer

Abstract: Metastasis is the major cause of death among gastric cancer (GC) patients, and altered expression of Ras-related protein RAP1B is associated with cancer development. The present study assessed RAP1B expression ex vivo and the effect of hypoxia‑induced RAP1B overexpression on the promotion of the metastatic potential of GC cells in vitro. Immunohistochemistry was used to detect the expression of RAP1B and hypoxia‑inducible factor-1α (HIF-1α) in 178 GC tissue specimens. GC cell lines were used to assess the effe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 33 publications
1
20
0
Order By: Relevance
“… 26 We have previous shown expression of RAP1B is associated with poor prognosis and promotes an aggressive phenotype in gastric cancer. 27 However, whether or not infiltration of TAMs is involved in EMT of human GC needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“… 26 We have previous shown expression of RAP1B is associated with poor prognosis and promotes an aggressive phenotype in gastric cancer. 27 However, whether or not infiltration of TAMs is involved in EMT of human GC needs further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, to determine the performance of OSeac, three published EAC prognostic biomarkers were assessed in OSeac, and all of them reach statistical significance for prognosis in OSeac as expected, indicating the good performance of OSeac in prognostic biomarker screening. OSeac could also be used to screen novel prognosis biomarker for EAC, for example, RAP1B contributes to tumor malignant behavior and poor prognosis in GC (24). Using OSeac to assess the prognostic value of RAP1B in EAC, we found that RAP1B is a potential unfavorable prognostic indicator for EAC patients.…”
Section: Discussionmentioning
confidence: 92%
“…In addition, to further test the prediction power of OSeac, we choose a known prognostic marker of gastric cancer (GC) (24) to analyze it in OSeac. We examined prognostic potency of RAP1B for EAC patients by OSeac, and found that RAP1B was significantly associated with unfavorable OS in TCGA (P = 0.0464, HR: 2.0045, 95% CI: 1.0111-3.9741), GSE13898 (P = 0.0241, HR: 3.0920, 95% CI: 1.1596-8.2446) and GSE19417 (P = 0.0138, HR: 2.4119, 95% CI: 1.1965-4.8618).…”
Section: Discovering Potential Biomarkers For Eac In Oseacmentioning
confidence: 99%
“…Of these 442 proteins, 102 ( t ‐test <0·05) and 20 (B‐H adjusted t ‐test P < 0·05) proteins were differentially expressed between the two patient groups (all 102 are listed in Table SII) (Fig ). Sixty‐five proteins were overexpressed in the REF/REL group and several of these proteins (Elongation factor 1‐beta, 14‐3‐3 protein gamma, nucleophosmin 1, RAP1B, Heat shock protein 60 and IMP dehydrogenase 2) have previously been described as negative prognostic factors or involved in drug resistance in other malignancies (De Bortoli et al , ; Li et al , ; Raungrut et al , ; Zhou et al , ; Yang et al , ; Sawazaki et al , ). Two proteins overexpressed in the REF/REL group have been reported as a negative prognostic marker or associated with multidrug resistance in DLBCL: Y‐box protein 1 (Miao et al , ) and pontin/RuvBL1 protein (Nishiu et al , ).…”
Section: Resultsmentioning
confidence: 99%